2018
DOI: 10.12911/22998993/86145
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization/Solidification of Tailing on Traditional Gold Mining in Kulon Progo Using Fly Ash

Abstract: Traditional gold mining activity is one of the sources of mercury contamination. Total mercury concentration in tailing ponds in Kulon Progo ranged from 164.49 mg/kg to 383.21 mg/kg, which exceeded the quality standard values set by the government of Indonesia No. 101 of 2014, which is 75 mg/kg. One method that can be applied is stabilization/solidification (S/S). This study aims to determine the optimum composition of the tailing mixture with fly ash in S/S process. The variations of fly ash composition with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A public gold mining area in Kulon Progo, Indonesia, has been operated for decades. The untreated tailing waste is directly discharged at several collection ponds around the mine site (Pamayo and Trihadiningrum, 2015, Rachman et al, 2017, Rachman et al, 2018. Kalimantoro (2016) reported that the mercury concentration in soil around the mining site was 164-384 mg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…A public gold mining area in Kulon Progo, Indonesia, has been operated for decades. The untreated tailing waste is directly discharged at several collection ponds around the mine site (Pamayo and Trihadiningrum, 2015, Rachman et al, 2017, Rachman et al, 2018. Kalimantoro (2016) reported that the mercury concentration in soil around the mining site was 164-384 mg/kg.…”
Section: Introductionmentioning
confidence: 99%